PENURUNAN STRES FISIK DAN PSIKOSOSIAL PASIEN PRE-OPERASI BEDAH ONKOLOGI MELALUI MEDITASI TERAPI DI SALAH SATU RUMAH SAKIT DI KOTA PADANG - -, Renidayati (Fakultas Keperawatan Universitas Andalas, 2016)
Generally, the patients will undergo the surgery will feel stress, both physical and psychological stress (anxiety). It is very dangerous because of the high heart rate and blood pressure will aggravate cardiovascular system. This study aimed to determine